An angle velocity of blade and lift force relationship of the single rotor system - Al Al (International Journal of Science, Engineering, and Information Technology, 2019)
Problems in utilizing Quadcopter, either as a hobby or as special needs are still many obstacles or weaknesses such as; plane easy to fall; plane easy hit; the battery is not durable; vulnerable to weather conditions and others. In this regard, Quadcopter's research and development has grown to include weaknesses of existing Quadcopter planes and to improve aircraft facilities and capabilities. In developing the knowledge and information about the Quadcopter aircraft, the data or parameters related to aircraft lift capability factors; fly long; flying high; type of motor used; the type of propeller used; including the sensors and control systems used. Thus, this study was to find the relationship between changes in the BLDC motor voltage source to the rotor angle velocity (ω); Change of rotor speed to wind velocity through rotor (v); change of rotor speed to rotor lift (Ft); change of wind speed to rotor lift; push the following rotor (Ct). In this study, empirical testing was conducted in the laboratory to determine the relationship among others: changes in the BLDC motor voltage source to the rotor angle velocity (ω); Change of rotor speed to wind velocity through rotor (v); change of rotor speed to rotor lift (Ft); change of wind speed to rotor lift; push the following rotor (Ct). Test and measurement results data show that; the relationship between lift power generated with rotational speed is not proportional Nonlinearity occurs when the rotor is released from the self and starts pulling the strain gauge when the rotation speed reaches around 65 rps. Once the rotation speed of the rotor is able to reach up to 1.5 Newton lift then the thrust rising trend increasing sharply to the increasing the speed of rotation of the rotor. A special rotor that has BLDC motor specifications such as; 1200 KV, 5 Volt and 30 Ampere; blade with a radius of r 0.12 m; at a temperature of about 27 oC; in the condition there are no other wind currents then obtained thrust (Ct) of 1.732.  Keywords: Rotation Speed, Thrust Coefficient, Quadcopter.